The Effect of Dhikr Therapy on Anxiety Levels in the Elderly at UPT PSTW husnul Khotimah, Riau Province - Nurdian Sasmita; Suci Amin; Tengku Isni Yuli Lestari Putri; Rahmaniza Rahmaniza (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2026)
Background & Objective: Anxiety is a common psychological problem among the elderly that can reduce quality of life if left unmanaged. Dhikr therapy is a non-pharmacological spiritual intervention that may help alleviate anxiety. Methode: This study aimed to determine the effect of dhikr therapy on anxiety levels among elderly individuals at UPT PSTW Husnul Khotimah, Riau Province. A quantitative pre-experimental one-group pretest–posttest design was used with 61 elderly respondents selected through purposive sampling. Anxiety levels were measured using the Indonesian version of the Zung Self-Rating Anxiety Scale (ZSAS). Dhikr therapy was administered for three consecutive days, and data were analyzed using the Wilcoxon Signed Rank Test. Result: The results showed a significant reduction in anxiety levels after the intervention (p < 0.05). Conclusion: In conclusion, dhikr therapy is effective in reducing anxiety among the elderly and can be applied as a non-pharmacological nursing intervention in elderly care settings.